COVID-19 infection risk by open and laparoscopic surgical smoke: A systematic review of the literature. Issue 6 (December 2021) - Antunes, Diandra; Lami, Mariam; Chukwudi, Agbim; Dey, Abhishek; Patel, Mahul; Shabana, Amanda; Shams, Mohamed; Slack, Zoe; Bond-Smith, Giles; Tebala, Giovanni
Abstract: Background: The current COVID-19 pandemic has greatly changed the way surgery is delivered. In particular, current guidelines and policies have highlighted the need to use high level Personal Protective Equipment to reduce the risk of viral infection during open and laparoscopic surgical procedures. In particular, it was felt that the laparoscopic approach was at higher risk of viral transmission due to the chimney effect of the smoke escape from the trocars during and after the procedure. However, with this being a new and largely unknown viral agent, guidelines have been based on speculation and extrapolation from previous studies conducted in completely different situations, and led to anxiety amongst surgeons and theatre staff. We decided to conduct a systematic review of the Literature to try to clarify whether inhalation of surgical smoke can increase the risk of COVID-19 infection. Methods: A thorough search of the relevant Literature was performed following the PRISMA guidelines and the most relevant papers on this topic were selected for qualitative analysis. Duplicates, review, personal opinions and guidelines have been excluded. Quantitative analysis has not been performed due to the lack of homogeneous high-quality studies. Results: Literature search identified 740 papers but only 34 of them were suitable for qualitative analysis. The quality of those studies is generally quite low. We were not able to find any evidence directly linking surgical smoke with viral transmission, other than in patients with active HPV infection. Discussion: Inhalation of surgical smoke can be generally hazardous, and therefore the use of PPE during surgical operations must be recommended in any case. However, the present systematic review of the existent Literature did not identify any significant evidence of the risk of viral transmission with the surgical smoke, therefore the current guidelines restricting the use of laparoscopy and/or diathermy during the current Covid-19 pandemic may be considered excessive and non-evidence based. Highlights: Clinical studies supporting current guidelines on COVID-19 have yet to be done. Previous evidence suggesting HBV, HIV and HPV virus detection in plumes is low level. There is currently no evidence of COVID-19 viral transmission risk via surgical smoke. Current guidelines may be considered excessive and non-evidence based.